Regional drivers and characteristics of multi-year droughts - Jonna van Mourik; Denise Ruijsch; Karin van der Wiel; Wilco Hazeleger; Niko Wanders (Weather and Climate Extremes)
Multi-year droughts (MYDs) are severe natural hazards that have become more common due to climate change. Given their significant societal impact compared to droughts of shorter duration, it is crucial to better understand the drivers of MYDs. Using reanalysis data, this study provides a historical overview of MYDs in California, Western Europe, India, central Argentina, South Africa, and southeast Australia. For each region, the characteristics and drivers of the multi-year droughts are given and compared to those of normal droughts (NDs). Additionally, we investigated the potential for longer-term memory of droughts. Our findings reveal that MYD occurrence and duration vary significantly per region, with relatively larger differences in duration between MYDs and NDs observed in California, Argentina, and Australia. Regions with distinctive seasonality in their precipitation climatology tend to experience faster drought onsets compared to regions with climatologically steady precipitation. Our analysis shows that MYDs and NDs often start with similar conditions but diverge over time, with larger potential evapotranspiration values for most regions, and additional lower precipitation rates for Argentina and India. Longer-term memory is present in Argentina, Australia, and South Africa, which might provide avenues for the predictability of MYDs in these regions. Teleconnections influenced by oceans and land are expected to play a significant role here, while in other regions MYD occurrence may be more subject to chance. These findings can aid in decision-making on water management, preceding and during droughts.